Prevalence, management and ethnobotanical investigation of hypertension in two Guinean urban districts. (1st March 2019) - Diallo, M.S.T.; Traore, M.S.; Balde, M.A.; Camara, A.K.; Baldé, E.S.; Traore, S.; Oulare, K.; Diallo, T.S.; Laurent, S.; Muller, R.N.; Tuenter, E.; Pieters, L.; et al.
Abstract: Ethnopharmacological relevance: Hypertension is an important public health challenge in low- and middle-income countries, and in many African countries including Guinea medicinal plants are still widely used for its treatment. Materials and Methods: The objective of this study was to determine the prevalence of hypertension in two Guinean urban districts (Pounthioun and Dowsare), to describe its management and to collect information on traditional herbal remedies. A total of 316 participants entered the study, 28.2% (89/316) men and 71.8% (227/316) women. Of these, 181 were from Dowsare (50 men and 131 women) and 135 from Pounthioun (39 men and 96 women). The mean age of subjects was 40.8 ± 14.0 years (range18 − 88years), while the majority of subjects (63.3% or 200/316) were 45–74 years old. Results: The overall prevalence of hypertension was 44.9% (142/316): 46.4% (84/181) from Dowsare and 43.0% (58/135) from Pounthioun. Ethnobotanical investigations among hypertensive patients led to the collection of 15 plant species, among which Hymenocardia acida leaves and Uapaca togoensis stem bark were the most cited. Phytochemical investigation of these two plant species led to the isolation and identification of isovitexin and isoorientin from H. acida, and betulinic acid and lupeol from U. togoensis. Conclusion: The presence of these constituents in Hymenocardia acida leaves and Uapaca togoensis stem bark may at least in part support their traditional use against hypertension in Guinea. Graphical abstract: